AVALIAÇÃO CLÍNICA DA INFLUÊNCIA DO CAFÉ NA EFETIVIDADE DO CLAREAMENTO DENTAL - Siqueira, Márcia Fernanda de Rezende (2012)
The objective of this clinical study was to evaluate whether exposure to coffee during the bleaching treatment with PC 16 (Whiteness Perfect, FGM,Joinville, Santa Catarina, Brazil) affects the degree of whitening and tooth sensitivity. We selected 40 patients with central incisors darker than A2, which were divided into 2 groups (n=20): GC - control group and GE - the experimental group. For the CG was no restriction of foods with dyes and the GE patients beyond the usual coffee intake in his diet made with black coffee rinses soluble Nescafé® Tradição (Nestlé), 4 times daily for 30 seconds. For both groups we used PC 16 for a period of 3 hours daily for 3 weeks. The color scale was assessed by spectrophotometer Easyshade and in the periods: initial, during the whitening (1 st, 2 nd and 3 rd week) and postbleaching (1 week and 1 month). Patients recorded their perceptions of sensitivity through the NRS scale (0-4) and VAS. For the color analysis was performed analysis of variance (ANOVA) with repeated measures on two factors (time vs. treatment groups), time being the repeated measure (=0.05). We carried out the Tukey test for contrast of means (=0.05). The tooth sensitivity was evaluated by Fisher's exact test and the intensity of tooth sensitivity was evaluated by Mann-Whitney test (=0.05) for both scales. There effectiveness of tooth whitening over time (p <0.001). For both groups was not statistical differences in absolute risk of sensitivity between the groups (p=1.0). Most patients had mild tooth sensitivity and no statistically significant difference was detected between groups for both the NRS scale (p=0.529) and for the VAS (p=0.258). It was concluded that dental bleaching is effective for the groups studied, which makes possible the consumption of coffee during the bleaching treatment.